The Intertwined Dialogues of Peace and Forgiveness in Uncle Tom's Cabin - Pasopati, Rommel Utungga; Napitupulu, Johanes Claudio Perdana; Puspayani, Komang Sinta; Damayanti, Ni Putu Nia; Faulina, Maulidia Nur (CV. Tripe Konsultan, 2024)
Crimes and peace are interdependent yet paradoxical to each other. The absence of crime can affect peace, accuracy and vice versa. This two-sided paradox can in fact be reconciled through forgiveness as a door to wider freedom. In Uncle Tom's Cabin novel, Tom forgives Legree, Sambo, and Quimbo who tortured him to death. Tom does not avenge violence with violence but with forgiveness. When Tom almost died, Legree did not care about his condition. In reverse, Sambo and Quimbo were impressed by Tom's heart and turned to take care of him. Tom's forgiveness shows ethical intention of others as in Levinas's thought, promise of peace and wider freedom in the sense of Ricoeur, and possibility of the heterogeneity of everyday life according to de Certeau. Tom's forgiveness at once shows everyone, no matter how small he is, can forgive others. This allows further reconciliation in a reciprocal way. Circle of violence can be cut off by forgiveness that heals others. Briefly, Tom is a reflection of peace in the form of forgiveness. Forgiveness means healing others, widening the circle of freedom of others, and as a promise of peace. Forgiveness can open itself up to reconciliation by promising freedom for a new life.